STRATEGI HUMAS SIBER DALAM MENINGKATKAN KUALITAS PELAYANAN INFORMASI PUBLIK 4.0 DI BADAN KEPEGAWAIAN NEGARA - Gabriel Gifson Hasugian; Yani Hendrayani; Lusia Handayani (Universitas Prof. Dr. Moestopo (Beragama), 2020)
This research is motivated use of cyberspace or online activities in providing public information services, especially of the 4.0 era which raises the issue of fakenews and the needs quickly information. The purpose of this research is to find out how the Badan Kepegawian Negara public relations strategy in improving the quality of public information services in the 4.0 era. The research method used is a qualitative with descriptive study analysis by collecting data through interviews. Concepts used are government public relations, cyber public relations quality, public services, 7-C public relations strategies and computer mediated communication. Research results show that BKN public relations have done a study of information service 4.0 in the use of cyber public relations websites, social media such as Twitter, Facebook, Instagram, YouTube, and canal complaints that is LaporBKN!. Cyber public relations strategies to improve service quality by adjusting the audience, infographics and schemes, packaging messages according to the audience, publishing with audio visual, polling public information services as an evaluation with the use of cyber public relations. Based on the results of research that the service with the use of cyber public relations run by BKN public relations is already good.